Application of Problem-Based Learning Model and Role Play Assisted by Moneybag Media to Improve Financial Literacy of Elementary School Students - Rahayu, Sri; Salsabila, Helmina; Wahyuny, Indra (Pijar : Jurnal Penelitian Bidang Pendidikan dan Pembelajaran, 2025)
Financial literacy is a crucial life skill encompassing knowledge, attitudes, and behaviors related to managing finances wisely. However, the financial literacy level of second-grade students in Class 2A at State Elementary School Kebonsari 3 Malang City remains low. This study aims to enhance students’ financial literacy through the implementation of a Problem-Based Learning model integrated with the Role Play method, supported by the use of Moneybag media in the topic "Wise Use of Money." The research employs a Classroom Action Research (CAR) approach conducted over three cycles. Data were collected through observation, questionnaires, and documentation, and analyzed using descriptive quantitative methods. The findings indicate a progressive improvement in students’ financial literacy scores, increasing from an average of 63.14 in the first cycle to 66.57 in the second cycle. The integration of Moneybag media in the second cycle yielded a completion rate of 75%, surpassing the predetermined success criterion of 70%. Further enhancements in the third cycle, achieved through the incorporation of the Role Play method, resulted in a significant increase in the completion rate to 89.38%, categorized as very good. These results provide practical insights for elementary school educators in designing interactive and contextual financial literacy instruction. Theoretically, the study reinforces the effectiveness of combining Problem-Based Learning and Role Play in fostering foundational financial competencies among young learners.